Antioxidant, Analgesic and CNS Depressant Activities of Commelina diffusa Burm. f. (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Commelina diffusa Burm. f. is a member of Commelinaceae family, which is widely grown in crop land and treated as a weed. This plant has several important medicinal properties which have not been studied extensively. In this study, the crude powder of C. diffusa whole plant was extracted with 95% ethanol and different solvent fractions (n-hexane, chloroform and methanol) were prepared from the crude extract by solvent-solvent partitioning. All these plant samples were subjected to bioassays for evaluating the antioxidant, central analgesic, peripheral analgesic and CNS depressant activities. The crude extract and its methanol soluble fraction showed mild free DPPH scavenging property with IC50 values of 98.49- and 84.77-μg/ml, respectively as compared to the standard ascorbic acid (IC50 = 2.67 μg/ml). In the analgesic activity test, the n-hexane fraction of C. diffusa at doses of 200- and 400-mg/kg body weight exhibited significant (p